Measurement of individual red blood cell motions under high hematocrit conditions using a confocal micro-PTV system - Lima, R. (2010)
Developments in optical experimental techniques have helped in elucidating how blood flows through microvessels. Although initial developments were encouraging, studies on the flow properties of blood in microcirculation have been limited by several technical factors, such as poor spatial resolution and difficulty obtaining quantitative detailed measurements at such small scales. Recent advances in computing, microscopy, and digital image processing techniques have made it possible to combine a particle tracking velocimetry (PTV) system with a confocal microscope. We document the development of a confocal micro-PTV measurement system for capturing the dynamic flow behavior of red blood cells (RBCs) in concentrated suspensions. Measurements were performed at several depths through 100-mm glass capillaries. The confocal micro-PTV system was able to detect both translational and rotational motions of individual RBCs flowing in concentrated suspensions. Our results provide evidence that RBCs in dilute suspensions (3% hematocrit) tended to follow approximately linear trajectories, whereas RBCs in concentrated suspensions (20% hematocrit) exhibited transversal displacements of about 2% from the original path. Direct and quantitative measurements indicated that the plasma layer appeared to enhance the fluctuations in RBC trajectories owing to decreased obstruction in transversal movements caused by other RBCs. Using optical sectioning and subsequent image contrast and resolution enhancement, the system provides previously unobtainable information on the motion of RBCs, including the trajectories of two or more RBCs interacting in the same focal plane and RBC dispersion coefficients in different focal planes.